(untitled) (The Research of Medical Science Review, 2025)
The increasing trends of obesity and breast cancer in the Punjab province of Pakistan are therefore portend for the future health, health care reform and socioeconomic advancement of the province. This socioecological form of inflammation and adipokine imbalances as mediating factors of primary and metastatic growth is highly relevant for primary prevention, early diagnosis, and intervention approaches in the province. This perspective from Punjab can prove useful for understanding the lessons from precision cancer control efforts in other LMICs struggling to contain increasing breast cancer rates. Knowledge of these mechanistic connections and their environmental modifiers is therefore important in the development of rational interventions, especially in the province of Punjab, in Pakistan, where both breast cancer and obesity are raging epidemics. First of all, minimizing the hormonal and metabolic risk factors in the development of BC, as well as optimizing the use of hormone-related biomarkers in clinical practice, can significantly reduce the incidence of this cancer crisis among Punjabi women. In conclusion, the risk factors associated with obesity, such as hormonal imbalances, chronic inflammation, and insulin resistance, may contribute to the development and progression of breast cancer among women in Punjab.